Can medical students accurately predict their learning? A study comparing perceived and actual performance in neuroanatomy. Issue 5 (1st April 2016) - Hall, Samuel R.; Stephens, Jonny R.; Seaby, Eleanor G.; Andrade, Matheus Gesteira; Lowry, Andrew F.; Parton, Will J.C.; Smith, Claire F.; Border, Scott
Abstract : It is important that clinicians are able to adequately assess their level of knowledge and competence in order to be safe practitioners of medicine. The medical literature contains numerous examples of poor self‐assessment accuracy amongst medical students over a range of subjects however this ability in neuroanatomy has yet to be observed. Second year medical students attending neuroanatomy revision sessions at the University of Southampton and the competitors of the National Undergraduate Neuroanatomy Competition were asked to rate their level of knowledge in neuroanatomy. The responses from the former group were compared to performance on a ten item multiple choice question examination and the latter group were compared to their performance within the competition. In both cohorts, self‐assessments of perceived level of knowledge correlated weakly to their performance in their respective objective knowledge assessments ( r = 0.30 and r = 0.44). Within the NUNC, this correlation improved when students were instead asked to rate their performance on a specific examination within the competition (spotter, rS = 0.68; MCQ, rS = 0.58). Despite its inherent difficulty, medical student self‐assessment accuracy in neuroanatomy is comparable to other subjects within the medical curriculum. Anat Sci Educ 9: 488–495. © 2016 American Association of Anatomists.